Response of cardiac autonomic modulation after a single exposure to musical auditory stimulation - Ferreira, Lucas L. [UNESP] (2015)
The acute effects after exposure to different styles of music on cardiac autonomic modulation assessed through heart rate variability (HRV) analysis have not yet been well elucidated. We aimed to investigate the recovery response of cardiac autonomic modulation in women after exposure to musical auditory stimulation of different styles. The study was conducted on 30 healthy women aged between 18 years and 30 years. We did not include subjects having previous experience with musical instruments and those who had an affinity for music styles. The volunteers remained at rest for 10 min and were exposed to classical baroque (64-84 dB) and heavy metal (75-84 dB) music for 10 min, and their HRV was evaluated for 30 min after music cessation. We analyzed the following HRV indices: Standard deviation of normal-to-normal (SDNN) intervals, root mean square of successive differences (RMSSD), percentage of normal-to-normal 50 (pNN50), low frequency (LF), high frequency (HF), and LF/HF ratio. SDNN, LF in absolute units (ms (2) ) and normalized (nu), and LF/HF ratio increased while HF index (nu) decreased after exposure to classical baroque music. Regarding the heavy metal music style, it was observed that there were increases in SDNN, RMSSD, pNN50, and LF (ms (2) ) after the musical stimulation. In conclusion, the recovery response of cardiac autonomic modulation after exposure to auditory stimulation with music featured an increased global activity of both systems for the two musical styles, with a cardiac sympathetic modulation for classical baroque music and a cardiac vagal tone for the heavy metal style.